1998
DOI: 10.1104/pp.118.3.875
|View full text |Cite
|
Sign up to set email alerts
|

Altered Zn Compartmentation in the Root Symplasm and Stimulated Zn Absorption into the Leaf as Mechanisms Involved in Zn Hyperaccumulation in Thlaspi caerulescens

Abstract: We investigated Zn compartmentation in the root, Zn transport into the xylem, and Zn absorption into leaf cells in Thlaspi caerulescens, a Zn-hyperaccumulator species, and compared them with those of a related nonaccumulator species, Thlaspi arvense. 65 Zncompartmental analysis conducted with roots of the two species indicated that a significant fraction of symplasmic Zn was stored in the root vacuole of T. arvense, and presumably became unavailable for loading into the xylem and subsequent translocation to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
209
1
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(224 citation statements)
references
References 33 publications
13
209
1
1
Order By: Relevance
“…Thus, AtFRD3 is needed to maintain root-to-shoot Fe mobility [12,61]. It is possible that in A. halleri and T. caerulescens, FRD3 contributes to Fe homeostasis and, in particular, to Fe mobility in the presence of xylem Zn concentrations that are likely to be substantially higher than in non-accumulator species like A. thaliana [62]. The need for a higher metal chelation capacity in the xylem could also explain the high transcript levels of FRD3 in the hyperaccumulators.…”
Section: The Transport Of Chelators and Metal Chelatesmentioning
confidence: 99%
“…Thus, AtFRD3 is needed to maintain root-to-shoot Fe mobility [12,61]. It is possible that in A. halleri and T. caerulescens, FRD3 contributes to Fe homeostasis and, in particular, to Fe mobility in the presence of xylem Zn concentrations that are likely to be substantially higher than in non-accumulator species like A. thaliana [62]. The need for a higher metal chelation capacity in the xylem could also explain the high transcript levels of FRD3 in the hyperaccumulators.…”
Section: The Transport Of Chelators and Metal Chelatesmentioning
confidence: 99%
“…The percentage of viable protoplasts in the stock was determined by staining with FDA (Fluka) as described by Lasat et al (1998). A stock solution of 7.2 mm FDA dissolved in acetone was prepared.…”
Section: Determination Of Protoplast Viabilitymentioning
confidence: 99%
“…An important trait of hyperaccumulating species might be enhanced translocation of the absorbed metal to the shoot. Time course studies of Zn accumulation revealed that T. caerulescens exhibited a 10-fold greater Zn translocation to the shoot as compared with Thlaspi arvense (Lasat et al, 1996), which was correlated with a 5-fold increase of Zn in xylem sap (Lasat et al, 1998). These authors have performed compartmentation studies and have found that 65 Zn uptake by leaf protoplasts is also stimulated in T. caerulescens compared with T. arvense.…”
mentioning
confidence: 95%
“…The genetics and the biochemical processes involved in metal uptake, transport, and storage by hyperaccumulating plants are still poorly understood, although this basic information is fundamental for the improvement of the technique (Van Der Lelie et al, 2001). Zn is one of the most important metal contaminant in industrialized countries (Nriagu and Pacyna, 1988), and numerous studies have been conducted on the species Thalspi caerulescens (Vazquez et al, 1992(Vazquez et al, , 1994Pollard and Baker, 1996;Lasat et al, 1998Lasat et al, , 2000Kü pper et al, 1999;Salt et al, 1999;Frey et al, 2000;Assunçaõ et al, 2001) and, to a lesser extent, on Arabidopsis halleri (Macnair et al, 1999;Bert et al, 2000;Kü pper et al, 2000;Zhao et al, 2000). This latter species is of particular interest because it is one of the closest relatives to Arabidopsis (Koch et al, 2001), whose genome is entirely sequenced (Meinke et al, 1998;Kaul et al, 2000).…”
mentioning
confidence: 99%